Instytucja prawna zadatku z punktu widzenia ekonomicznej analizy prawa - Tenenbaum-Kulig, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The article concerns the institution of deposit and civil responsibility, which are examined using Economic Analysis of Law. The author aims at answering the question whether the Economic Analysis of Law is an attractive method, which could be used in civil law research and tries to find its benefits for use in the analysis of the institution of deposit in Polish civil law. The analysis of the institution of deposit utilises some elements of economic theories, like the Coase Theory, the Rational Choice Theory and the Game Theory. The conclusion is that some kinds of typical economic mechanisms could be used in civil law research, because applying them simplifies evaluating civil law institutions as affective or not.
Keywords: zadatek; odpowiedzialność cywilna; ekonomiczna analiza prawa